Zeno’s Debt to Hippasus - Panchenko, Dmitri (Hyperboreus, 2018)
The way of argumentation employed by the Eleatic philosophers was repeatedly compared with methods of demonstration characteristic for Greek mathematics. The paper addresses a particular type of argument, argumentum ad impossibile, found in both Zeno’s antinomies and an ancient demonstration of the incommensurability of the side and diagonal of a square. It is argued that in this particular case the debtor was Zeno.